2011
DOI: 10.1016/j.csda.2010.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Robust weighted kernel logistic regression in imbalanced and rare events data

Abstract: Benchmark datasets optimal parameter values with balanced training sets.. 6.3 Benchmark datasets bootstrap accuracy (%) comparison using balanced training sets. Bold accuracy values indicate the highest accuracy reached

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 118 publications
(72 citation statements)
references
References 64 publications
0
68
0
4
Order By: Relevance
“…Rare events have occurrence frequencies that are low (Maalouf and Trafalis, 2011), with the number of events in the dataset dozens to thousands times smaller than the number of non-events. King and Zeng (2001a, b) have shown that rare events are difficult to predict as the standard application of logistic regression techniques can sharply underestimate the probability for rare events.…”
Section: Introductionmentioning
confidence: 99%
“…Rare events have occurrence frequencies that are low (Maalouf and Trafalis, 2011), with the number of events in the dataset dozens to thousands times smaller than the number of non-events. King and Zeng (2001a, b) have shown that rare events are difficult to predict as the standard application of logistic regression techniques can sharply underestimate the probability for rare events.…”
Section: Introductionmentioning
confidence: 99%
“…Adding a dither to a signal is an established technique for improving the accuracy of a subsequent quantizer output [29]. This takes advantage of bias reduction while increasing the linear separability as well as the classification accuracy [15,26]. Also, the amplitude of the forcing function increases and the oscillations become random after dithering.…”
Section: The Effect Of Ditheringmentioning
confidence: 99%
“…In addition, Maalouf et al proposes a robust weighted kernel logistic regression. It can correct the bias of logistic regression in imbalanced classification [15].…”
Section: Imbalanced Classificationmentioning
confidence: 99%